General Principles of Anti-Corruption in V4 Visegrad Countries: Experience of Hungary (Law and Safety, 2020)
Corruption in Hungary poses a significant risk to business, especially in the tax administration and public procurement sectors, which suffer from its high level. The public procurement process and the tendering process are insufficiently protected from irregularities at the local level due to strong informal relations between business and representatives of government at the local level. Public opinion polls on general and specific corruption issues show that a third of Hungarians consider corruption and abuse of power to be widespread in Hungary’s public administration system.The purpose of this article is to clarify the origins of the formation and to study general experience in implementing activities aimed at preventing and combating corruption in one of the countries of V4 Visegrad Group – Hungary, a neighbor of Ukraine, post-socialist country and member of the European Union since 2004, as well as to analyze its results and the possibility of implementing certain provisions into national legal system.The author has clarified the place of Hungary and Ukraine in the world rankings as the result of the study, in particular in the Corruption Perceptions Index. The author has studied the data of sociological research conducted in Hungary to identify the most corrupt areas of public life, to determine the attitude of the population to the level of corruption and willingness to participate in its reduction, as well as to summarize the factors that led to such results.The activities of certain Hungarian state organizations that directly or indirectly prevent and combat corruption, including the Ombudsman, the State Audit Office and the National Defense Service of Hungary, have been considered. The legal basis for the implementation of anti-corruption policy from international acts to the National Program for the Prevention of Corruption in Public Administration has been determined.The author has made an attempt to summarize the reasons for the decrease in the level of effectiveness of the implementation of the anti-corruption strategy and recommendations aimed at improving its effectiveness.
Keywords: corruption; Hungary; Ukraine; counteraction to corruption; anti-corruption activities; fight against corruption